PENGARUH MOBILISASI DINI TERHADAP PENYEMBUHAN LUKA POST OPERASI SECTIO CAESARIA DI RS SYAFIRA PEKANBARU TAHUN 2015 - WIWIEK DELVIRA; FATMI AGUS (JURNAL PROTEKSI KESEHATAN, 2015)
Maternal mortality used as a measure of success towards achieving the MDG's targets, namely the 75% reduction in maternal mortality ratio. In developing countries the frequency of maternal deaths reported to range between 0.3-0.7%, while in developed countries the figure is smaller, which 0.05-0.1% (Widjanarko, 2008). In accordance with the health paradigm without abandoning efforts to restore the health of patients, the need for early mobilization gradually for sectio caesarea postoperative patients while in hospital. The purpose of this study was to determine the effect of early mobilization on wound healing post sectio caesarea in RS Syafira Pekanbaru. The benefits of this research are as fulfilling the Minimum Service Standards (MSS) for the hospital that can be used as eviden based practice in the provision of nursing services independently. This study was conducted in inpatient obstetric in RS Syafira Pekanbaru on October-November 2015 with a sample of 20 respondents. The research methodology used is the cross-sectional study design. Analysis of the data used in the analysis of univariate and bivariate (t test dependent), the data were processed using a computerized program. The results obtained from this research that the influence of early mobilization with postoperative wound healing secsio Caesaria with P value (0.007).